Plularisme Islam: Mewujudkan Sikap Inklusif Dan Toleran Antarumat Beragama Di Indonesia - Aril Purnama (Himmah: Jurnal Kajian Islam Kontemporer, 2021)
An understanding of the plurality of the Indonesian people is not enough just to know and accept the fact that our society is indeed diverse, consisting of various ethnicities and religions, which only depicts the impression of fragmentation. Because pluralism is not understood in depth, it has implications for the problem of the principle of tolerance. As a result of this, in Indonesia itself, there was a Muslim crisis, for example, which was marked by terrorism carried out by organizations or individuals in the name of Islam.In this article, the author tries to examine how Islamic values, especially in terms of pluralism, in realizing an inclusive and tolerant society in Indonesia based on the study of literature and the author's own perspective.